DEPC modification of the Cu(A) protein from Thermus thermophilus - Devlin, Taylor (J Biol Inorg Chem, 2018)
The Cu(A) center is the initial electron acceptor in cytochrome c oxidase, and it consists of two copper ions bridged by two cysteines and ligated by two histidines, a methionine, and a carbonyl in the peptide backbone of a nearby glutamine. The two ligating histidines are of particular interest as they may influence the electronic and redox properties of the metal center. To test for the presence of reactive ligating histidines, a portion of cytochrome c oxidase from the bacteria Thermus thermophilus that contains the Cu(A) site (the TtCu(A) protein) was treated with the chemical modifier diethyl pyrocarbonate (DEPC) and the reaction followed through UV–visible, circular dichroism, and electron paramagnetic resonance spectroscopies at pH 5.0–9.0. A mutant protein (H40A/H117A) with the non-ligating histidines removed was similarly tested. Introduction of an electron-withdrawing DEPC-modification onto the ligating histidine 157 of TtCu(A) increased the reduction potential by over 70 mV, as assessed by cyclic voltammetry. Results from both proteins indicate that DEPC reacts with one of the two ligating histidines, modification of a ligating histidine raises the reduction potential of the Cu(A) site, and formation of the DEPC adduct is reversible at room temperature. The existence of the reactive ligating histidine suggests that this residue may play a role in modulating the electronic and redox properties of TtCu(A) through kinetically-controlled proton exchange with the solvent. Lack of reactivity by the metalloproteins Sco and azurin, both of which contain a mononuclear copper center, indicate that reactivity toward DEPC is not a characteristic of all ligating histidines.